2022
DOI: 10.1177/21582440211067220
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of SME’s Social Media Marketing Adoption: Competitive Industry as a Moderator

Abstract: In light of the growing role of social media marketing in the success of businesses and its low adoption rate among small and medium enterprises (SMEs), this study aims to identify determinants of SMEs’ social media marketing adoption by considering the competitive industry as a moderator. Data were collected from 214 SMEs in Malaysia. Unlike extant literature, this study proposed a dual-stage analysis involving partial least squares (PLS) technique and artificial intelligence named deep artificial neural netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 103 publications
(205 reference statements)
8
67
1
1
Order By: Relevance
“…For the significance of hypothesized relationships in the proposed model, researchers in this study have used PLS-SEM software. PLS-SEM has been adopted due to several reasons, such as it can test complex models ( Ali Abbasi et al, 2022 ; Ashaari et al, 2021 ; Henseler, Ringle & Sarstedt, 2015 ; Chin, Marcolin & Newsted, 2003 ), does not involve normality, small sample size, and able to work without distributional assumptions ( Abbasi et al, 2021 ). Along with symmetrical analytical tools (PLS-SEM) to explore the combinations of causal factors (causal complexities of four factors) leading to the outcome (people autonomy), asymmetrical modelling was performed by using fsQCA ( Ragin, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the significance of hypothesized relationships in the proposed model, researchers in this study have used PLS-SEM software. PLS-SEM has been adopted due to several reasons, such as it can test complex models ( Ali Abbasi et al, 2022 ; Ashaari et al, 2021 ; Henseler, Ringle & Sarstedt, 2015 ; Chin, Marcolin & Newsted, 2003 ), does not involve normality, small sample size, and able to work without distributional assumptions ( Abbasi et al, 2021 ). Along with symmetrical analytical tools (PLS-SEM) to explore the combinations of causal factors (causal complexities of four factors) leading to the outcome (people autonomy), asymmetrical modelling was performed by using fsQCA ( Ragin, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the past decade, the use of partial least squares structural equation modeling (PLS-SEM) has attracted numerous interests and especially in investigations that are at the interface of digital adoption and organizational research (Abbasi et al, 2022;Alziady and Enayah, 2019;Bharati et al, 2014;Foltean et al, 2019;Li and Wang, 2018;Vatanasakdakul et al, 2020), hence a reason to use PLS-SEM since it makes this study more comparable to others. Moreover, because this work is based on in-sample prediction, in addition to the extension of the institutional theory to a context that has never been before investigated and coupled with the fact that the adoption of social media is a more recent phenomenon, the use of PLS-SEM is and social media adoption analytically valid.…”
Section: Analyticmentioning
confidence: 99%
“…While there is a growing recognition of the positive role that social media can play in the firm (Abbasi et al, 2022;Eid et al, 2019), social media adoption by the small-sized firm, as compared to large firms, remains relatively low till date (Namankani et al, 2016;Deloitte Touche Tohmastum, 2017;Statista, 2021a). For instance, a business survey conducted in the European Union (EU) revealed that only 48% of small firms use social media in the EU (Statista, 2021a), while in Australia and New Zealand it was found that only one in five small firms regularly use social media to engage with consumers (Deloitte Touche Tohmatsu, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfying and retaining the customer is always challenging, as customer retention has become more challenging in the E-Comm ( Abbasi et al., 2022 ). Personal mobile devices offer the facility to contact people and use internet services on the go for multiple activities ( Jay and Zhang, 2016 ).…”
Section: Introductionmentioning
confidence: 99%